Popular culture in contemporary Zimbabwe Towards fostering a national cultural identity through music performance - Wonder Maguraushe; Isaac Machafa (Midlands State University Press, 2023)
In the year 2001 Zimbabwe promulgated the Broadcasting Services Act that mandated radio and television stations to play 75 percent local music. This local content policy was a loud statement of the government’s sustained efforts to fight western cultural imperialism. Over the years this policy led to a proliferation of local artists playing a plethora of music genres. This study set out to examine the role of music in fostering a Zimbabwean national identity. In order to achieve this objective, this study used the methods of media ethnography (radio and television), an empirical description and analysis of Zimbabwean music genres which emanated from extensive fieldwork as we interacted with musicians, fans, and music academics whom we purposively sampled in Zimbabwe. From a globalisation perspective, we trace the local and international creation of a Zimbabwean identity through music brands that have been marketed locally and throughout the world. Findings reveal that respondents experience a cultural bond when they listen to sungura, Zimbabwean dance-hall, Zimbabwean hip-hop, mbira, marimba, chimurenga and gospel music genres on the country’s soundscape. We argue that musical cultural representations in popular culture play a significant role in citizens’ construction of a Zimbabwean national identity in a highly dynamic globalised world.